2023
DOI: 10.1161/jaha.122.028332
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Poor Mental Health With Cardiovascular Disease and Suboptimal Cardiovascular Health Among Young Adults in the United States

Abstract: Background Depression is a nontraditional risk factor for cardiovascular disease (CVD). Data on the association of depression and poor mental health with CVD and suboptimal cardiovascular health (CVH) among young adults are limited. Methods and Results We used data from 593 616 young adults (aged 18–49 years) from the 2017 to 2020 Behavioral Risk Factor Surveillance System, a nationally representative survey of noninstitutionalized US adults. Exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Our findings about overall associations between depression and mortality risk are consistent with previous study results . A study using the 1999 National Health Interview Survey linked with mortality data through 2011 showed that, adjusting for demographic factors, anxiety or depression was associated with 61% elevated risk of mortality .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings about overall associations between depression and mortality risk are consistent with previous study results . A study using the 1999 National Health Interview Survey linked with mortality data through 2011 showed that, adjusting for demographic factors, anxiety or depression was associated with 61% elevated risk of mortality .…”
Section: Discussionsupporting
confidence: 91%
“…In 2020, an estimated 21 million US adults (8.4%) had at least 1 major depressive episode . Numerous adverse outcomes have been associated with depression, including increased cardiovascular disease (CVD) incidence and premature mortality . The onset of CVD occurs an average of 7.5 years earlier in adults with mood disorders, and people with severe mental disorders, including moderate to severe depression, die an average of 10 to 20 years earlier than the general population .…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with other studies that have posited MDD as a significant risk factor for adverse cardiovascular events. [34][35][36] The elevated rates of STEMI and NSTEMI in this group further underscore the critical need for targeted cardiovascular monitoring in patients with MDD. Furthermore, data revealed that the highest major amputation rate was in patients with both OUD and MDD, followed by those having only OUD and No MDD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple physiological pathways, including disruptions in glucose and lipid regulation, as well as abnormalities in the coagulation cascade due to chronic stress, serve as mechanisms through which psychological well-being influences cardiovascular health and CVD risk 42. Hence, prioritising mental health may assist in CVD risk reduction in young adults 43…”
Section: Discussionmentioning
confidence: 99%